A comparison of on-pack Quitline information formats - Hoek, Janet; Gendall, Philip; Eckert, Christine; Rolls, Kirsty; Louviere, Jordan (Tobacco control, 2016)
BackgroundAlthough tobacco packages have evolved to feature health warnings and, in Australia, dissuasive colours, the format of on-pack cessation information has not changed. We compared how alternative Quitline information formats affected smokers’ perceptions and choice behaviours, and their likelihood of seeking cessation support.MethodsWe conducted an online study comprising a choice experiment using a two (number of panels) by three (panel position: above, middle, below) plus control (current format) design, and a between-subjects comparison of a two-panel format and the control. The sample comprised 608 New Zealand smokers.ResultsRelative to the current format, respondents regarded each test format as more effective in communicating cessation information (p<0.0001), particularly the two-panel formats. Respondents found the two-panel format tested via paired comparisons significantly easier to read, more visually salient and more likely than the control to encourage them and other smokers to consider quitting (all p<0.0001). Heat map comparisons showed that the Quitline number and affirming message were significantly more salient in the test format than in the current format (p<0.0001), although the headline and warning explanation were more salient in the control.ConclusionsReformatting Quitline information could improve its visual salience and readability and capitalise on the dissonance that pictorial warning labels and plain packaging create. Enhancing stimuli that may prompt smokers to try and quit, affirming their decision to do so and prompting the use of cessation support could increase the number and success of quit attempts.